Decision Support System for Choosing The Best Housing Location by The Satisficing Model and AHP Method - Eva Tri Ningsih (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Residence is the most important means of life as a place to gather with family and build a peaceful and harmonious family. The realization of community welfare and quality human resources can be characterized by an improvement in the standard of living. This research took an alternative location to the villages located in Rumbai district, namely Sri Meranti, Umban Sari, Palas, Lembah Damai, Limbungan Baru, Meranti Pandak. The criteria used are at least 6 criteria with the AHP Method and Satisficing Model. The Analytical Hierarchy Process (AHP) method compares based on human perception, the AHP method can be strengthened by the Satisficing Models method because the Satisficing Models method in this case is a comparison method that calculates real financial or economic value with the human perception method. Thus, it can be concluded from this application and research that the Satisficing Models Method is a supporting method or method to strengthen the feasibility of the AHP method. The AHP method compares only six sides of the compared criteria in this DSS, while the Satisficing Models method compares all six financial aspects. In this case, the recommended alternative location to select is the one with the highest rating result in the AHP method - The Satisficing Model.